The effects of oxygen concentration on cell death, anti-oxidant transcription, acute inflammation, and cell proliferation in precision-cut lung slices - Ruigrok, Mitchel J. R. (Sci Rep, 2019)
Although animal models are often used in drug research, alternative experimental models are becoming more popular as they reduce animal use and suffering. Of particular interest are precision-cut lung slices, which refer to explants – with a reproducible thickness and diameter – that can be cultured ex vivo. Because lung slices (partially) reflect functional and structural features of whole tissue, they are often applied in the field of immunology, pharmacology, toxicology, and virology. Nevertheless, previous research failed to adequately address concerns with respect to the viability of lung slices. For instance, the effect of oxygen concentration on lung slice viability has never been thoroughly investigated. Therefore, the main goal of this study was to investigate the effect of oxygen concentration (20 vs. 80% O(2)) on the degree of cell death, anti-oxidant transcription, acute inflammation, and cell proliferation in lung slices. According to the results, slices incubated at 20% O(2) displayed less cell death, anti-oxidant transcription, and acute inflammation, as well as more cell proliferation, demonstrating that these slices were considerably more viable than slices cultured at 80% O(2). These findings expand our knowledge on lung slices and their use as an alternative experimental model in drug research.